MASK: A CREATIVE REPRESENTATION OF FUNCTIONAL ART - Pandey, Dr. Anjali (International Journal of Research -GRANTHAALAYAH, 2019)
Masks are used all over the world for their expressive power. It is an important part of theatre and rituals. It is generally used to conceal the identity or to transform the character. In India the festival mask are used to represent the deities and mythological character in dance and drama performance as well as in many ceremonial functions, religious and social rituals and in entertainment since ancient time. The evidences of mask could also be seen since prehistoric age. Many tribes of India mask are used in rituals and performances. The masks of different region are distinct and peculiar in size, shape, form, design and material used. In early era the masks were made in simplified form, now some innovative decorations have changed their aesthetic value.